Core–shell metal–organic frameworks and hierarchical host–guest structures toward water-stable luminescence of lanthanide complexes in encoding beads. Issue 32 (14th July 2020) - Mo, Dong; Wang, Zhengqiang; Sun, Kaiyao; Xie, Xiyue; Zhang, Jixi; Cai, Kaiyong
Abstract : Hetero-MOF domains in hybrid core–shell nanoparticles realize encapsulation and protection of lanthanide complexes for water-stable photoluminescence, facilitating hierarchical encoding beads with a 3D host–guest structure. Abstract : The photoluminescence stability of lanthanide complexes (Lnx) in biological media is of the utmost significance for the construction of optically encoded nano-on-microbeads in multiplex bioassays. Herein, we propose a new type of encoding guest consisting of MOF@MOF nanohybrids, where isomorphic ZIF-8 and ZIF-90 were employed as the core and shell domain, respectively, to separately modulate the hosting and the protection of the inner Lnx guests. Especially, the thin ZIF-90 shell epitaxially grown on the ZIF-8 core was employed as an intermediate layer to facilitate surface covalent fluorination via an aldehyde ligand. Thereby, a superhydrophobic surface was obtained, which led to strong water-resistance of the hybrid nanoparticles, stable host–guest structure, and high quantum yields (19.1%) in biological media. A coating layer of a surface active polymer (polydopamine, PDA) was utilized to conjugate the MOF nanoparticles on polystyrene microspheres for building the second-level host–guest architecture of 3D core–satellite pluralistic hybrids. Finally, single/dual-color encoded beads (EBs) were obtained by altering the ratios of the hybrid MOF guests emitting at different wavelengths. As a proof of concept, the detection of a model tumor marker (alpha-fetoprotein, AFP) was successfully performed using the encoded beads. These findings can pave the way for the rational design of core–shell MOFs and hierarchical structures with high synergy and excellent flexibility toward stable photoluminescence of lanthanide complexes in bioassays.